因為∠ABE+∠AEB=90°,∠CED+∠AEB=90°,所以∠ABE=∠CED.
于是Rt△ABE∽Rt△CED,(4分)
所以
S△CDE |
S△EAB |
CE |
AB |
1 |
4 |
CE |
CD |
AB |
AE |
又∠ECF=∠DCF=45°,所以CF是∠DCE的平分線,點F到CE和CD的距離相等,
所以
S△CEF |
S△CDF |
CE |
CD |
所以S△CEF=
2 |
3 |
2 |
3 |
1 |
4 |
2 |
3 |
1 |
4 |
1 |
2 |
1 |
24 |
![](http://hiphotos.baidu.com/zhidao/pic/item/9358d109b3de9c821437133e6f81800a19d84335.jpg)
解法2:如圖,作FH⊥CE于H,設FH=h.(2分)因為∠ABE+∠AEB=90°,∠FEH+∠AEB=90°,所以∠ABE=∠FEH,
于是Rt△EHF∽Rt△BAE.(4分)
因為
EH |
FH |
AB |
AE |
1 |
2 |
又因為HC=FH,所以h=
1 |
2 |
1 |
6 |
所以S△CEF=
1 |
2 |
1 |
2 |
1 |
2 |
1 |
6 |
1 |
24 |
![](http://hiphotos.baidu.com/zhidao/pic/item/d009b3de9c82d1580ad0b300830a19d8bc3e4235.jpg)